2021
DOI: 10.1039/d1cc03474j
|View full text |Cite
|
Sign up to set email alerts
|

MXene/WS2hybrids for visible-light-activated NO2sensing at room temperature

Abstract: OPTOELECTRONIC GAS SENSORS BASED ON TWO-DIMENSIONAL (2D) MATERIALS ARE TOUTED AS POTENTIAL CANDIDATES FOR NO2 SENSING AT ROOM TEMPERATURE. HOWEVER, MOST OF THE DEVELOPED OPTOELECTRONIC SENSORS TO DATE ARE CONFINED...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Two-dimensional (2D) nanostructured materials can offer a large surface-to-volume ratio, high surface energy and numerous active reaction sites on the surface, resulting in an excellent physicochemical activity. 19–21 Moreover, the construction of 2D/2D layered composites possess a large interfacial area owing to face-to-face contact and effective interfacial charge transfer ability. 22,23 Thus, in this work, we selected ultrathin BiVO 4 nanosheets with a high redox potential 24 as the host photocatalyst and reduced graphene oxide (rGO) as the cocatalyst.…”
mentioning
confidence: 99%
“…Two-dimensional (2D) nanostructured materials can offer a large surface-to-volume ratio, high surface energy and numerous active reaction sites on the surface, resulting in an excellent physicochemical activity. 19–21 Moreover, the construction of 2D/2D layered composites possess a large interfacial area owing to face-to-face contact and effective interfacial charge transfer ability. 22,23 Thus, in this work, we selected ultrathin BiVO 4 nanosheets with a high redox potential 24 as the host photocatalyst and reduced graphene oxide (rGO) as the cocatalyst.…”
mentioning
confidence: 99%
“…In recent years, a variety of 2D-materials-based optoelectronic devices have been designed and experimentally demonstrated due to their promising optical and electrical properties. Next, we will introduce some developed 2D-materials-based optoelectronic devices, including photodetectors, ,, sensors, , and transistors, in the following subsections.…”
Section: Metaphotonic Devices Based On 2d Materialsmentioning
confidence: 99%
“…In addition, 2D-materials-based optoelectronic gas sensors have been intensively investigated recently (refs , , , , and ). For example, Pham et al proposed and experimentally demonstrated a graphene–MoS 2 optoelectronic gas sensor for low-concentration NO 2 gas sensing …”
Section: Metaphotonic Devices Based On 2d Materialsmentioning
confidence: 99%
“…NO 2 gas sensors that can work at room temperature are particularly important because they have the advantages of low power consumption, no heating, and easy operation [ 2 , 3 ]. So far, many different types of NO 2 gas sensors that work at room temperature have been manufactured by using different sensitive materials [ 4 , 5 , 6 , 7 , 8 ]. Among them, wearable NO 2 gas sensors have the characteristics of flexibility, a light weight, and a low cost and important application potential and value in the field of wearable electronics [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%